Patience! How to Assess and Strengthen Self-Control - Hauser, Marc D. (Frontiers in Education, 2019)
Children often show signs of dysregulation, impulsivity, and risk-taking  behaviors that interfere with learning and growth. Commonly implicated in such interfering behaviors are problems of self-control. Several decades of research in the mind and brain sciences inform understanding of self-control, both as a trait and state. This research has significant implications for educators, providing strategies for assessing and strengthening self-control. This paper reviews the relevant theoretical concepts and practical applications. Part one discusses current thinking about the nature of self-control, focusing on the paired distinctions between (i) trait and state, as well as (ii) volitional and impulsive processes. Part two reviews a family of methods designed to assess different aspects of self-control. Part three focuses on ways to strength self-control, including simple strategies that help create habits and reduce conflict with competing temptations.